Tinjauan Yuridis Perlunya Pengaturan Hukum LGBT dari Perspektif Hukum Adat dan Hukum Islam di Indonesia - Lydyana Trisnaeni Martin; Nur Aulia Lathifah; Eka Era Nurtanti; Kheisa Rahma Adhadina; Savira Eka Kusumawati (Lembaga Pengembangan Kinerja Dosen, 2024)
Juridically in the context of Indonesian law, there are two perspectives that can be used to discuss the need for LGBT legal regulations, namely the customary law perspective and the Islamic law perspective. Lesbian, Gay, Bisexual and Transgender (LGBT) groups in Indonesia have received significant attention. This research uses normative legal research techniques as its methodology. This research further examines the need for clear legal regulations regarding LGBT. Considering the fact that Indonesia is a legal country where people respect each other's customs and religious beliefs, it can be said that the legalization of LGBT people is not justified. Thus, it is hoped that this research can answer problems that are of concern to the Indonesian people. As well as, it can open insight that legal regulations regarding LGBT in Indonesia are very necessary to achieve benefits, certainty and legal justice.